Integrating Green Nanotechnology into Higher Education: A Pragmatic Framework for Enhancing Environmental Curricula and Sustainability in Libyan Institutions (مجلة الفاروق للعلوم, 2026)
This paper proposes a structured curriculum framework for integrating green nanotechnology into undergraduate science and engineering programs in Libyan higher education institutions. Drawing on the principles of green chemistry and sustainability-oriented pedagogy, the framework addresses a persistent tension in resource-constrained academic laboratories: the need to provide rigorous, hands-on scientific training while reducing reliance on hazardous reagents, energy-intensive procedures, and waste streams that many institutions are not equipped to manage safely (Anastas & Warner, 1998; O’Neil et al., 2021; UNESCO, 2017). The proposed model is organized around a three-phase laboratory sequence: preparation of aqueous plant extracts from locally available species, principally Olea europaea (olive) and Punica granatum (pomegranate); biogenic synthesis of metallic nanoparticles; and application of the resulting materials to the photocatalytic degradation of model organic dye pollutants. Each phase is linked to core undergraduate physical chemistry concepts, including reduction kinetics, surface capping, colloidal stability, and surface plasmon resonance (SPR) (Duan et al., 2015; Iravani, 2011; Nasrollahzadeh et al., 2019). By grounding these concepts in observable laboratory phenomena, the framework supports active, inquiry-based learning rather than passive instruction (Hmelo-Silver et al., 2007; Krajcik & Shin, 2014).The paper is conceptual and design-based. It does not report experimental outcomes; instead, it offers a theoretically grounded model whose empirical validation is identified as a necessary next step. Its main strengths lie in low cost, alignment with local agricultural and environmental conditions, and the ability to connect scientific training with pressing environmental challenges, including dye-contaminated wastewater and sustainable materials development (Makhalanyane et al., 2020; Singh et al., 2018). The paper situates the proposal within the broader context of higher education reform in Libya and calls for systematic pilot implementation across multiple institutions, with attention to learning outcomes, protocol reproducibility, and waste reduction metrics.